Material Design of Functionally Graded Plates with the Function of Electromagnetic Noise Suppression: Quantitative Evaluation of the Effect of Electromagnetic Noise Suppression - SUGANO, Yoshihiro; TAKAHASHI, Satoshi (Journal of Solid Mechanics and Materials Engineering, 2008)
The development of materials to suppress electromagnetic noise is in demand. In this paper, we present a method for the material design of functionally graded material (FGM) plates with the function of electromagnetic noise suppression. The FGM plates are considered to be multilayered plates in which the material properties are homogeneous inside each layer. Therefore, the approximate analytical solutions of electromagnetic fields in the FGM plates subject to electromagnetic noise are derived. The expressions for electromagnetic noise suppression are then obtained based on the above analytical solutions. Numerical calculations are carried out for epoxy resin/titanium oxide FGM plates with graded composition distribution expressed in the form of a power function. The effects of graded composition and plate thickness on the electromagnetic noise suppression are quantitatively evaluated, and the material design suitable for the suppression of electromagnetic noise is discussed.